Efektivitas pemutaran lagu Indonesia Raya dalam program televisi: Upaya memupuk jiwa patriotisme di kalangan generasi muda - Mubarok, M. Faza Akmalul (Maliki Interdisciplinary Journal, 2025)
The playing of the national anthem "Indonesia Raya" in television programs plays a significant role in fostering patriotism, especially among the younger generation. This study aims to analyze the effectiveness of the broadcast of "Indonesia Raya" in television programs as a means of instilling nationalism. The method used is a literature review, collecting data from various credible sources, including journals, articles, and relevant research reports. The findings of this study suggest that although "Indonesia Raya" is often played in television programs, its impact on enhancing the patriotism of the younger generation remains questionable, especially due to the influence of social media and globalization. This study provides important contributions to the understanding of the impact of mass media on national values and the crucial role of television in shaping national character.